Pembinaan Kultural Calon Jamaah Haji melalui Tradisi Mandi Sesucen di Desa Jangga, Losarang–Indramayu - Lutfiyanah Lutfiyanah; Abdul Rozak; Agus Riyadi (Kamaya: Jurnal Ilmu Agama, 2025)
This study aims to analyze the cultural coaching for prospective hajj pilgrims through the sesucen bath ritual in Jangga Village, Losarang District, Indramayu Regency. This ritual is a form of spiritual purification performed prior to the hajj pilgrimage as a preparation for inner readiness. The research employed a qualitative method with a descriptive-analytical approach. Data were collected through observation, interviews, and documentation. The findings reveal three main aspects. First, the sesucen bath ritual is carried out through several stages: the shalat safar prayer, recitation of ruqyah verses, purification bathing, religious briefing by local clerics, joint prayer, the call to prayer, and walking on a shroud cloth as a symbol of spiritual protection. Second, the pilgrims understanding of the ritual varies; some perceive it as a valid form of spiritual strengthening based on Qur’anic verses, while others regard it as an unnecessary additional practice not required by Islamic law. Third, the cultural coaching encompasses four dimensions: cultural-religious, social-relational, managerial, and religious moderation. The study concludes that a cultural coaching grounded in religious moderation effectively maintains a balance between Islamic values and local cultural traditions, offering strategic recommendations for religious leaders to prepare hajj pilgrims who are spiritually, socially, and managerially ready without neglecting their cultural roots.